PENGARUH HASIL PRAKTIK KERJA LAPANGAN (PKL) TERHADAP MINAT BERWIRAUSAHA SISWA PROGRAM KEAHLIAN TATA BOGA - Novida Wahyu Riani (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2020)
The purpose of this study is to find out (1) the effect of the industrial practical work result to the entrepreneurship interest (2) description of entrepreneurship interest and (3) the result of industrial practical work. Type of study is ex-post fact. The type of data collection used questionnaire and documentation. Descriptive analysis technique and hypothesis testing using the Product Moment correlation test which is preceded by tests of normality and linearity. The result of study shows that there is effect of industrial practical work result to the students’ entrepreneurship interest. The total contribution of the industrial practical work to the students’ entrepreneurship interest was 49.9%, meanwhile 50.1% was influenved by other factors which were not discussed in this study.